2017
DOI: 10.1111/sjop.12371
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control depletion impairs goal maintenance: A meta‐analysis

Abstract: Initial exertion of self-control has been suggested to impair subsequent self-regulatory performance. The specific cognitive processes that underlie this ego depletion effect have rarely been examined. Drawing on the dual-process theory of executive control (Engle & Kane, ; Kane & Engle, ), the current meta-analysis revealed that initial self-control exertion impairs participants' capacities of maintaining the task goal but its effect on capacities of resolving response competition is in need of further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
(78 reference statements)
1
16
0
2
Order By: Relevance
“…In a subsequent meta-analysis Carter et al ( 2015 ) examined effect size as a function of the outcome task used, showing that carry-over depletion effects differed across tasks, but again, when bias-correction techniques were adopted, effect sizes were not distinguishable from zero. Moreover, the most recent meta-analysis focused solely on the Stroop Task and found little evidence to support the strength model, and what evidence there was, was contaminated by publication bias (Dang et al, 2017 ).…”
Section: “Replication Crisis”mentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent meta-analysis Carter et al ( 2015 ) examined effect size as a function of the outcome task used, showing that carry-over depletion effects differed across tasks, but again, when bias-correction techniques were adopted, effect sizes were not distinguishable from zero. Moreover, the most recent meta-analysis focused solely on the Stroop Task and found little evidence to support the strength model, and what evidence there was, was contaminated by publication bias (Dang et al, 2017 ).…”
Section: “Replication Crisis”mentioning
confidence: 99%
“…For example, a demonstration that no change in behavior occurred in the depletion task over time but carry-over effects did emerge, would present strong disconfirming evidence for the strength model (Baumeister et al, 1998 , 2007 ). On the other hand such an outcome would not be problematic for models that attribute depletion effects to task switching aspects of cognitive control, where it is the nature of the two tasks that is important, not what happens within each task (Dang et al, 2013 , 2017 ). Moreover, examining what happens in the depletion task is important from a methodological perspective.…”
Section: “Conceptual Crisis”mentioning
confidence: 99%
See 1 more Smart Citation
“…Future research is needed to develop a more comprehensive theory that could reconcile the strength model, the process model, as well as related cognitive models of ego depletion (Dang, Björklund, et al, 2017;Dewitte, Bruyneel, & Geyskens, 2009).…”
Section: Addressing Conceptual Issuesmentioning
confidence: 99%
“…We added this extension block because prior research has suggested that the 50/50 mixture of congruent and incongruent trials (as was done in the original study) has been known to elicit a phenomenon known as goal neglect (Kane & Engle, 2003; see also Dang, Björklund, , & Bäckström, 2017), a temporary loss of the task goal (i.e., color naming) from working memory due to the abundance of cues supporting an inappropriate task goal (in this case, word reading, due to the large number of congruent trials for which word reading suffices). In contrast, a 50/50 mixture of incongruent and neutral (asterisk) trials used in Block 2 would make the Stroop task more appropriate as a measure of overriding dominant yet inappropriate responses.…”
Section: Materials and Proceduresmentioning
confidence: 99%